Pengaruh Globalisasi Kepadatan Penduduk dan Pertumbuhan Ekonomi terhadap Degradasi Lingkungan di Indonesia - Safriwan Safriwan; Idris Idris (Universitas Negeri Padang, 2021)
The study describes the effects on globalization population density and economic growth on environmental degradation in Indonesia. This research uses a time series data from year 1971 - 2017, with method Error Correction Model (ECM). Data sources from Global Carbon Project, KOF Swiss Economic Institute, and World Bank. Research result explain that (1) Globalization in long term has a insignificant positive effect on environmental degradation in Indonesia, but short term globalization has a insignificant negative effect on environmental degradation in Indonesia (2) Population density in long term has a significant positive , and short term has a insignificant positive effect on environmental degradation in Indonesia (3) Economic growth in long and short term has a significant positive effect on environmental degradation in Indonesia.